1990
DOI: 10.1111/j.1471-0528.1990.tb02548.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of suture material on vaginal vault granulations following abdominal hysterectomy

Abstract: Summary. A questionnaire was circulated to 1147 members (consultant status) and fellows of the Royal College of Obstetricians and Gynaecologists to survey the current management of the vaginal vault following abdominal hysterectomy. Of the 56% who responded, the majority (87%) routinely close the vault. An interrupted mattress suture is used by 60%, a continuous suture by 43% and the Lembert suture by 2%. Chromic catgut is favoured by 60%, a synthetic polymer by 33% and plain catgut by 6%. We then organized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…When chromic catgut was used for the vaginal vault, granulation occurred in 10.8% of patients. When polyglactin was used, the frequency was reduced to 2.7% [21]. This might be due to the characteristically low tissue reaction during absorption associated with polyglactin.…”
Section: Discussionmentioning
confidence: 99%
“…When chromic catgut was used for the vaginal vault, granulation occurred in 10.8% of patients. When polyglactin was used, the frequency was reduced to 2.7% [21]. This might be due to the characteristically low tissue reaction during absorption associated with polyglactin.…”
Section: Discussionmentioning
confidence: 99%
“…found a lower morbidity rate with subtotal compared with total hysterectomy and reported that wound infections, haematomas and urinary tract infections may be less common. Vault granulations do not occur with subtotal hysterectomy while they complicate 21% of total hysterectomies 34 . However, in general, the British gynaecologist has a negative view to subtotal hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…As early as 1990's it was found that polygalactide, a synthetic polymer, is associated with fewer vaginal vault granulations than chromic catgut. 29 Staplers (absorbable) also has lower frequency of postoperative granulation tissue at the apex of the vaginal vault and vaginal discharge during 12 weeks of followup. 30 Siedhoff et al have observed a lower incidence of vaginal cuff dehiscence, postoperative bleeding, presence of granulation tissue and cuff cellulitis when bidirectional barbed suture was used in the laparoscopic vaginal suturing after hysterectomy and trachelectomy.…”
Section: Vault Granulation Tissuementioning
confidence: 99%